Answer:
x = 3/2Y + 7
Explanation:
1. Solve the paratheses. If you distribute 2/3 through the parentheses, you get Y+2=2/3x - 8/3.
2. You should then multiply both sides of the equation to get
3Y + 6 = 2x - 8
3. Move the variable to the left-hand side and change its side. You should get 3Y + 6 - 2x = -8. Then, move the expression to the right-hand side and change its sign. -2x=-8 - 3Y - 6
4. Calculate: -2x = -14 - 3Y
5. Divide both sides of the equation by 2: x = 7+3/2Y
6. Use the commutative property to reorder the terms: x = 3/2Y+7
So, your answer is 3/2Y + 7. Hope this helped!